The transformation of values into prices on the basis of random systems revisited: reply to my commentators - Bertram Schefold (Evolutionary and Institutional Economics Review, 2020)
This paper defends The Transformation of Values into Prices on the Basis of Random Systems, published in EIER, by answering to the Comments made in the same journal by Professors Mori, Morioka and Yamazaki. The clarifications mainly concern the justification of the randomness assumptions, the conditions needed to obtain the equality of total profit with total surplus value in the simplified one-industry system and the invariance of the results to changes in the units of measurement.
Keywords: B14; B24; B16; C65; D57; 330; Marxian economics; Transformation problem; Capital theory; Sraffian economics; Profits and distribution